Community Organization and Empowerment of Women: The Mujeres Pescadoras del Manglar Cooperative in Oaxaca, Mexico. Issue 4 (19th August 2021) - Sartini, Ilaria; Sánchez, Francisco Caravaca
Abstract: Gender equity is still a challenge for the world, especially in those regions where sociocultural practices permeated by machismo, that is, male chauvinism, intersect with poverty and institutionalized racial discrimination. The creation of safe and feminized spaces where women can express themselves freely is crucial in the process of cultivating their awareness of their own positions, and the first step toward individual and collective empowerment. In this article the authors point out the direct and positive relationship between feminine cooperativism and women's empowerment, taking as a case study the Mujeres Pescadoras del Manglar cooperative in Oaxaca, Mexico, a group of women who, thanks to a social work program implemented by La Ventana civic association, has been able to gain empowerment and recognition at a personal and political level. Likewise, Mujeres Pescadoras del Manglar is an example of the national phenomenon of bolstering female employment in the fishing sector, which is on the rise thanks to the growing number of women's cooperatives, through which they can access the labor market, feminize new spaces, and achieve full empowerment for themselves, their families, and the society in which they live. The fieldwork was carried out from November 2018 to February 2019 in the community of El Zapotalito, Oaxaca. The methodology used consists of semistructured interviews, life stories, field diaries, and participant observation. This article showcases a positive example of social work empowering low-income women on the Chica coast of Oaxaca.